First Identification and Molecular Characterization of Trichinella britovi (Nematoda: Trichinellidae) from the Pine Marten (Martes martes Linnaeus, 1758) in Romania - Ana-Maria Marin; Ovidiu-Alexandru Mederle; Gianluca Marucci; Dan-Cornel Popovici; Narcisa Mederle (Microorganisms, 2023)
Trichinella spp. are etiological zoonotic agents spread throughout the world and affect mammals, birds, and reptiles; they evolve via two cycles: domestic and sylvatic. Martes martes is a carnivorous nocturnal mammal from the family Mustelidae. In Romania, this host is widespread in all forests of the country. Martes martes has an extremely voracious appetite, feeding on fruit and also on a variety of small animals, including rodents such as mice and rats. The aim of this study was the identification and molecular characterization of Trichinella larvae isolated from the muscle tissue of Martes martes collected in different counties of Romania. The muscle samples were examined via artificial digestion, and the larvae were identified at the species level via multiplex PCR. The presence of larvae belonging to Trichinella britovi, a species frequently identified in wild carnivores in temperate zones, was observed. Although T. britovi has been already reported in several host species in Romania, this is the first time this species has been observed in a Martes martes specimen. This finding contributes to our knowledge about the host species involved in the maintenance of the Trichinella sylvatic cycle in Romania, and it confirms that this parasite is consistently present in the wild fauna of this country.